development of thermosynthesis technology in vibrating layer of powder microcomposites - V.G. LYULKO; K.K. SHUGAY; A.V. LYULKO; S.A. MALOFEEVA (Advanced Engineering Research, 2008)
Aspects of application of thermosynthesis technology in vibrating layer for composite powders with structural components mesa-, ultra- and nanodimensions for new niveua powders functional materials are discussed. It is submitted installation for thermosynthesis, the nomenclature of composite powders and examples nanostructures components on matrix powders of iron (Fe/P+Sn; Fe/P +Cu; Fe/Cu +P; Fe/P +Zn/ZnO) and ceramics (Al2O3-Cu/CuO).